Age- and sex-related development of osteosarcopenia in the aging Octodon degus rodent model - Gallo-Soljancic, Pablo; De Stefano, Maria Egle; Lucas-Ochoa, Ana-María; Sánchez-Rodrigo, Consuelo; Cuenca-Bermejo, Lorena; González-Cuello, Ana-María; Fernández-Villalba, Emiliano; Herrero, María-Trinidad (Frontiers in Aging, 2025)
The increase in life expectancy in recent years has resulted in a higher incidence of age-related diseases. Among these, osteoporosis and sarcopenia, collectively known as osteosarcopenia, have the most significant impact on the quality of life, general health and frailty in the elderly. As for other age-related diseases, pre-clinical studies on these conditions are primarily limited by the availability of experimental model systems. The Octodon degus (O. degus) is a long-lived diurnal rodent identified as a potential tool in ageing research. However, age-related osteosarcopenia changes have not yet been explored. In this study, male and female O. degus from juvenile to senile ages were used (6 months–7 years old). Changes in the volume of several forelimbs and hindlimbs muscles, e.g., biceps femoris, triceps brachii, femur, and humerus, were evaluated using computed tomography. Aged animals showed a significant decrease in muscle volume in both hindlimbs and forelimbs, along with a significant reduction in cortical bone volume. With ageing, sex differences were also observed, with female O. degus showing greater cortical bone volume in both hind and forelimbs, and greater muscle mass in the sole hindlimbs, compared to male. These findings enhance the characterization of O. degus as a model to study age-related pathologies, also considering sex differences, and lay down solid foundations for future studies that can address in more detail the molecular mechanisms underlying the initiation and progression of osteosarcopenia.